Routine Clinical Anti-Platelet Agents Have Limited Efficacy in Modulating Hypershear-Mediated Platelet Activation Associated with Mechanical Circulatory Support - Valerio, Lorenzo (Thromb Res, 2017)
INTRODUCTION: Continuous flow ventricular assist devices (cfVADs) continue to be limited by thrombotic complications associated with disruptive flow patterns and supraphysiologic shear stresses. Patients are prescribed complex antiplatelet therapies, which do not fully prevent recurrent thromboembolic events. This is partially due to limited data on antiplatelet efficacy under cfVAD-associated shear conditions. MATERIALS AND METHODS: We investigated the efficacy of antiplatelet drugs directly acting on three pathways: (1) cyclooxygenase (aspirin), (2) phosphodiesterase (dipyridamole, pentoxifylline, cilostazol), and (3) glycoprotein IIb–IIIa (eptifibatide). Gel-filtered platelets treated with these drugs were exposed for 10 min to either constant shear stresses (30 dyne/cm(2) and 70 dyne/cm(2)) or dynamic shear stress profiles extracted from simulated platelet trajectories through a cfVAD (Micromed DeBakey). Platelet activation state (PAS) was measured using a modified prothrombinase-based assay, with drug efficacy quantified based on PAS reduction compared to untreated controls. RESULTS AND CONCLUSIONS: Significant PAS reduction was observed for all drugs after exposure to 30 dyne/cm(2) constant shear stress, and all drugs but dipyridamole after exposure to the 30(th) percentile shear stress waveform of the cfVAD. However, only cilostazol was significantly effective after 70 dyne/cm(2) constant shear stress exposure, though no significant reduction was observed upon exposure to median shear stress conditions in the cfVAD. These results, coupled with the persistence of reported clinical thrombotic complication, suggest the need for the development of new classes of drugs that are especially designed to mitigate thrombosis in cfVAD patients, while reducing or eliminating the risk of bleeding.